The Internationalisation of Southern Africa Development Community’s Higher Education Curriculum - Chikuvadze, Pinias; Permana, Erwin Putera; Mutseekwa, Christopher (Jurnal Simki Pedagogia, 2025)
Southern African Development Community (SADC)’s internationalization of higher education curriculum presents substantial opportunities and challenges. This paper explores the multifaceted process of integrating global perspectives into the curriculum of higher education institutions across SADC region. The 62 journal research papers, selected through purposive sampling, were obtained from databases including Scopus, DOAJ, DHTE, and WoS. Using citation analysis and keyword co-occurrence, the paper explores key themes, trends and influential studies, articulating the discourse concerning opportunities and challenges around the internationalisation of SADC’s higher education curriculum. It identifies opportunities, which include enhanced global competitiveness, collaborative partnerships, cultural exchanges, innovation in research and supportive policy development. However, the paper also highlights policy inconsistency, resource constraints, quality assurance and cultural differences. The findings underscore the potential of internationalized curricula to enhance SADC’s higher education quality and relevance. Ultimately, this contributes to the region's socio-economic growth and global integration. In conclusion, the SADC region’s internationalization of higher education curriculum presents mutually significant opportunities and distinguished challenges. To maximize the benefits of internationalization, a concerted effort is required from member states to work together to create an enabling environment for international cooperation and exchange such that higher education institutions can unlock their full potential.